Age related muscle texture variation between Cobb-500 and Ross broiler strain (Journal of the Bangladesh Agricultural University, 2011)
Meat characteristics of Cobb-500 and Ross boiler strains in terms of histomorphometry of myocyte, fat tissue and connective tissue were studied. Two representative muscles from breast (Pectoralis thoracis and Supracoracoideus) and two from thigh (Ilitibialis lateralis and Iliotibialis cranialis) were selected. Thicker myofiber in breast and thinner myofiber in thigh were found in Ross strain. The perimysial thickness significantly differed among the muscles. The perimysial thickness of breast and thigh muscle at 28th day and thigh muscle at 35th day of Cob-500 were found higher that indicate more toughness of representative muscles. Thick and broad bundles of collagen fiber were observed in perimysium of Ilitibialis lateralis and thinner but broad bundles were in perimysium of Pectoralis thoracis muscle. At 35th day of age the endomysial thickness was found same in both strains but at 28th day of age it was higher in Cobb-500 than that of Ross strain. The intramuscular fat deposited mainly within perimysium as cluster and the number (per focus) and the size of adipocyte diameter was differed among the muscles. Adipocytes diameter was recorded highest (24.14±1.33 μ) in pectoralis thoracis muscle of Ross boiler and 22.01±1.74 μ second in position in Cobb-500. The lowest diameter 15.62±0.87 μ) was recorded in case of iliotibialis lataralis muscle of Ross boiler. Keywords: Age; Strain; Meat characteristics; Broiler DOI: 10.3329/jbau.v8i2.7936 J. Bangladesh Agril. Univ. 8(2): 265-269, 2010